Comparison of phenotypic and Whole Genome Sequencing (WGS)-derived antimicrobial resistance profiles of Salmonella typhi isolated from Blood cultures. (March 2022) - Bari, A.K.; Geetha, S.; Shamanna, V.; Darmavaram, S.; Govindan, V.
Abstract : Purpose: Enteric fever remains an enormous public health threat in low and middle-income countries. Enteric fever, caused by Salmonella enterica serovar Typhi (S. typhi), is a global public health concern due to increasing antimicrobial resistance (AMR). Characterization of S. typhi genomes for AMR and the evolution of different lineages, especially in countries where enteric fever is endemic such as India, will help in understanding the evolving drug resistance trends and its impact on therapy. The purpose of our study was to understand the evolving drug resistance pattern in healthcare settings. Methods & Materials: S. typhi were isolated from blood cultures, Identification and Susceptibility testing of the isolates was carried out using Vitek 2 Compact (V2C) (bioMérieux) gram negative identification cards and Vitek 2 AST-N280 cards respectively. Further confirmation of identification was done by serotyping with Polyvalent O, serotype2, 4 and 9 (Remel TM, India). Whole Genome Sequencing was done on Illumina platform. The annotated whole genome sequences were used for the prediction of antibiotic resistance genes with ResFinder. Results: A total of 92 isolates 10.86% (n=10), 1.08% (n=1), 11.95% (n=11) and 100% (n=92) resistance were observed for Ampicillin (AMP) Trimethoprim/Sulfamethoxazole (SXT), Ceftriaxone (CRO) and Ciprofloxacin (CIP) respectively. No resistance was observed in Chloramphenicol. Based on the WGS prediction for resistance genes the analysis detected blaSHV-12 (n=11), blaTEM-1D (n=1) for AMP resistance, dfrA7 (n=1), sul1 (n=1), sul2 (n=1) for SXT resistance, blaSHV-12 (n=11) for CRO resistance and qnrB (n=11) for CIP resistance. Additionally, we observed 7 SNPs (gyrAD87N, parCS801, gyrAS83F, ParED420N, ParEL416F, gyrAS83Y and gyrAD87G ) of the qnrB gene. 11 CIP resistant isolates had triple mutations (gyrAD87N, parCS801 and gyrAS83F ). Most common SNP found for CIP resistance are gyrAS83F (83.69%), gyrAD87N (58.69%), parCS801 (55.43%), gyrAS83Y (13.04%), ParED420N (4.34%), ParEL416F (4.34%) and gyrAD87G (1.08%). Conclusion: In our study we did not find any MDR salmonella. Of concern were 11 (11.95%) isolates which had triple mutant variant (gyrAD87N, parCS801 and gyrAS83F ) for high level CIP resistance and 3rd generation cephalosporin resistance due to blaSHV-12 .